CONCEPTUAL METAPHOR IN THE PARABLES ON THE GOSPEL OF LUKE: AN ENGLISH - INDONESIAN TRANSLATION STUDY - Tri Sukarsih, Ni Nyoman; Budirasa, Made; Artawa, Ketut; Mbete, Aron Meko (e-Journal of Linguistics; 2016: Vol. 10 No. 2 July, 2016)
This study aims at exploring the application of conceptual metaphors in the parable texts found in the Gospel of Luke and various strategies applied in the translation of conceptual metaphors from English into Bahasa Indonesia. The research utilizes qualitative method in the form of text analysis to analyze the translation product based on a parallel corpus derived from the English version of the New Living Translation Bible published in 2008 by Lembaga Alkitab Indonesia and its translation into Bahasa Indonesia . Metaphorical expressions in sub-corpus were identified using data reduction technique in the form of parable texts found in the Gospel of Luke, which were collected, selected, simplified and abstracted. The findings emerged from this study. Firstly, from the conceptual mapping all three categories of conceptual metaphor were discovered including orientational metaphor, ontological metaphors, and structural metaphor. Secondly, to overcome the problems of translating conceptual metaphors, the translators applied methods closely oriented towards target language (TL) based on a number of conceptual metaphors translation procedures. Translation techniques employed include the communicative translation method.
Keywords: conceptual metaphor, translation strategies, translation ideology